The Soviet and Russian Energy Industry as Objects of Western Sanctions: Political Rivalry or Economic Competition - Y. V. Borovsky (Vestnik MGIMO-Universiteta)
Since the late 1940s Western countries have regularly used sanctions, embargoes and other similar instruments to counter the development of the Soviet and, after 1991, the Russian energy industry. The author tries to answer two research questions: what provokes such a policy of the West: political rivalry or economic competition? Has the West changed its attitude to the Russian energy industry after the end of the Cold war? The first part of the study covers the years of the Cold war; the second part is devoted to the period following the collapse of the USSR. The article deals with generic approaches of Western countries to the Soviet and Russian energy industry, as well as their stances on major oil and gas pipelines, including the «Druzhba» (or the «Friendship») oil pipeline, the Soyuz gas pipeline, The «Urengoy – Pomary – Uzhhorod» (or the West-Siberian) gas pipeline, the Nord Stream 1,2 gas pipelines. The author came to the following conclusions. The main inspirer of sanctions and other restrictive measures of the West against the Soviet and Russian energy industry has always been the United States of America. The core motive of such behavior has been political rivalry, although in certain periods (for example, in the 1950s-1960s, 2010-ies) the United States may also be driven by economic competition or the desire to ensure the interests of its energy companies. Western European countries have often been in solidarity with the American actions against the Soviet or Russian energy complex. However, when their strategic interests are affected (for example, in case of construction of the Urengoy – Pomary – Uzhgorod and Nord stream 2 gas pipelines), they can resist the dictates of Washington. This is due both to pressure from Western European business interested in cooperation with the USSR or Russia in the energy field, and a strong desire of Western European countries to diversify oil and gas supplies from the Middle East and to solve some other energy problems, for instance, to mitigate transit risks associated with Ukraine. Overall, the end of the Cold war has not radically changed the policy of the West towards the Russian energy industry.